Амбагай Хотулыг хаан болгохоор захисан уу ? Did Ambaqai qahan order that Qutula be king ? - Гэрэлбадрах, Ж. (Acta Mongolica, 2005)
It is widely accepted in the field of Mongolian historical studies that the second qahan (king) of the Mongols, Ambaqai qahan, was captured by the Tatars and compelled to make his plans for succession known. Historians have argued that in accordance with Ambaqai qahan’s last testament, Qutula assumed the kingship of the Mongols. The present work suggests that this historical argument is in need revision. According to historical sources such as the “Secret history of the Mongols”, the “Compendium of chronicles”, and the “Altan tobci” of Lubsandanzan, Ambaqai qahan stated in his testament that either Qutu a or Qada’an will become qahan of Mongolia through the selection process of the meeting of nobles.